2014
DOI: 10.1002/aic.14457
|View full text |Cite
|
Sign up to set email alerts
|

Spray impact resistance of a superhydrophobic nanocomposite coating

Abstract: The performance of a polyurethane/organoclay superhydrophobic nanocomposite modified with perfluoroalkyl methacrylic copolymer in the presence of a high‐pressure air‐water spray which mimics an icing cloud impact is investigated in this study. To quantify the average velocites of droplets impacting the superhydrophobic samples, a computational study was performed. Such a study is important to understand the interaction between the jet and surface. Impacting velocities for three different testing conditions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…29 It was hypothesized that a nanocomposite coating with high adhesion strength and high mechanical robustness would also have high resistance to erosion when exposed to rain. Although the velocity of the impacting droplets was not varied in this study, during a previous study, when impacted with micro-scale droplets with velocities in the range of 3-15 m s À1 , 30 it was observed that impacting droplets were able to saturate surface asperities with water and cause a gradual transition from the non-wetting Cassie state to the wetting Wenzel state aer a period of a few dozen seconds. Due to the large droplets and high velocities used in this study, saturation occurred almost immediately in the current study.…”
mentioning
confidence: 64%
“…29 It was hypothesized that a nanocomposite coating with high adhesion strength and high mechanical robustness would also have high resistance to erosion when exposed to rain. Although the velocity of the impacting droplets was not varied in this study, during a previous study, when impacted with micro-scale droplets with velocities in the range of 3-15 m s À1 , 30 it was observed that impacting droplets were able to saturate surface asperities with water and cause a gradual transition from the non-wetting Cassie state to the wetting Wenzel state aer a period of a few dozen seconds. Due to the large droplets and high velocities used in this study, saturation occurred almost immediately in the current study.…”
mentioning
confidence: 64%
“…The former can occur upon exposure to harsh chemicals or other degradation route (e.g. highly basic conditions, or photocatalytic degradation), but can also degrade readily under ambient conditions over time [9,44,68]. Therefore, a thorough consideration of superhydrophobic resilience would include the stability of surface functionalisation, the compatibility between the surface coating and underlying material, in addition to the effect of any reactive species present within the local environment.…”
Section: Application Specific Challengesmentioning
confidence: 99%
“…The latter of these necessitates a surface structure composed of micrometre, or nanometre, sized features-which are fundamentally physically weak structures. Therefore, commercial products that impart superhydrophobicity tend to degrade overtime, deteriorating at a faster rate as the intensity of the application increases [9].…”
Section: Introductionmentioning
confidence: 99%
“…The nanocomposite coatings were engineered via the bioinspired polymerization of metal–dopamine clusters and subsequent surface modification (silanization) (Figures S1 and S2). We used two types of trialkyl silanes (i.e., 1 H ,1 H ,2 H ,2 H -perfluorooctyltriethoxysilane and its fluorine-free counterpart n -octyltriethoxysilane) as the precursors for surface silanization, as longer chain perfluorinated compounds (e.g., perfluorooctanoic acid or PFOA, perfluorooctanesulfonic acid or PFOS) are known to be toxic. The metal–organic coatings (MOCs) examined have been selected because the dopamine component provides near-universal adherence and affinity to most common liquids (e.g., polar liquids); the metal–chelation networks are chemically stable, active and modular; and tunable repellence to various liquids is achieved through the integrated low energy silane component and the high energy MOC component which can respond (i.e., flip-flop , of the silane molecules) to the surrounding liquids based on their polarity (i.e., f MOCs; see Materials and Methods in the Supporting Information). Therefore, the resulting surface chemistry is heterogeneous, where both low surface energy silanes and high surface energy MOCs coexist in close proximity.…”
Section: Introductionmentioning
confidence: 99%